Financial support for tourism development in Liangshan prefecture, China - Cai Changyan; Lim, Fui Yee Beatrice (Faculty of Business, Economics and Accountancy, 2021)
Liangshan Prefecture is located in southwest China. Liangshan Prefecture uses its unique climate advantages and superior natural conditions, relying on the construction of a seasonal headquarters base, and vigorously builds an international tourist attraction. This article first investigates the current situation of financial support for tourism development in Liangshan Prefecture, and analyzes the plight of financial support for tourism in Liangshan Prefecture; secondly, the VAR model is used to further study the relationship between tourism development and financial support in Liangshan Prefecture. The data uses ADF test (Augment Dichey Fuller test), cointegration test (Engel-Granger test), Granger test of causality, impulse response analysis and variance analysis. Finally, it puts forward the countermeasures and suggestions to improve the financial support for the development of tourism in Liangshan Prefecture, such as increasing government support, strengthening the financial role of policy banks and commercial banks, improving the quality of financial services, and exploring other financial support paths.